ANALISIS PEMASARAN JAGUNG MANIS DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Syifa Hadirawati; Yulianti Kalaba; Abdul Muis (Universitas Tadulako, 2020)
The objectives of the research were to find out the form of sweet corn marketing, the marketing margin of sweet corn, the prices share received by sweet corn farmers, and the level of efficiency achieved in sweet corn marketing in Sigi regency. Data was analyzed using marketing margin and marketing efficiency analysis. There were two marketing channels in Sigi regency i.e. farmers – trader collector – retailer – Customer (channel I); and farmer – retailer – customer (channel II). The marketing margin in channel I was IDR 9,900/kg while in the channel II was IDR 9,000/kg. The share of prices received by the farmers in the channel I was 34% while in the channel II 40%. The marketing efficiency of sweet corn in the channel I was 5.9% and in the channel II was 3.0%. This indicates that the marketing efficiency of sweet corn in Sigi Biromaru sub-district of Sigi regency is more efficient in the channel II due to its shorter chain leading to lower cost. Similarly, the total sales value of the channel II is also greater than that of the channel I. Keywords : Corn, Marketing, Marketing Channel, and Marketing of Corn.